Are YouTube Videos Useful in Robot-assisted Segmentectomy Education? - Coşgun, Tuğba; Doğruyol, Talha; Tezel, Çağatay (The Thoracic and Cardiovascular Surgeon, 2025)
Background Segmentectomy operation became a preferable operation for small lesions due to the importance of saving lung parenchyma. Using robotic technology has too many advantages for segmentectomy operations. Web sites such as YouTube have become educational tools for surgical trainees. The aim of our study is to analyze YouTube videos for accurate and up-to-date information about robotic segmentectomy operations.Methods The videos on www.youtube.com, which were reached on July 11, 2024, by using the keywords “robot segmentectomy” and “robotic segmentectomy lung,” were evaluated in this research. The videos were evaluated by using the Journal of the American Medical Association (JAMA) scoring system, Critical View of safety (CVS), and LAParoscopic surgery Video Educational GuidelineS (LAP-VEGaS).Results Eighty-one videos were included. Almost half of the videos (n = 42) were affiliated with university hospitals. Preoperative imaging was seen in 49% of all videos; however, the rates were 32% and 20.9% for patients' demographics and preoperative assessment information, respectively. Only 29.6% of the videos presented the placement of trocars during the presentation.Conclusion It has become possible to record high-quality videos easily with developing technology. However, our results showed that many of the videos do not include the parameters especially related to education. Our findings suggest that those videos are inadequate for trainees.
Keywords: LAP-VEGaS; robot; segmentectomy; youtube; critical view of safety; education